Determining key success factors in new product development : evidence from manufacturing companies in Malaysia / Wan Jamaliah Wan Jusoh - Wan Jusoh, Wan Jamaliah (Faculty of Business and Management ; UiTM Press, 2000)
This study examines key factors in new product development in Malaysia by providing empirical evidence on NPD practices and its determinants for success. Data were collected through a large scale mail survey from a cross section of 185 Malaysian manufacturing companies spanning 9 industries sector. Using Factor Analysis and Pearsons Product Moment Correlation Analysis, key factors leading to successful NPD were determined.